Studies on Subclinical Mastitis in Sirohi Goats in Southern Rajasthan with Reference to Prevalence and Diagnostic Aspects - Sharma, SK; Meena, Hitesh K; Joshi, Monika (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Mastitis is an economically important disease in goats. In the present study, a total of 100 quarter milk samples were collected from 50 apparently healthy Sirohi Goats in Udaipur district. The culture examination of these samples revealed the prevalence of subclinical mastitis in Sirohi goats as 26 (26/100) % and 34 (17/50) % on udder quarter basis and animal basis, respectively. The highest prevalence of subclinical mastitis was observed in 3rd lactation (50 %). Among the different isolates, staphylococci were found as most prevalent organism accounting for 37.50 (12/32) %, followed by streptococci 28.12 (9/32) %, E. coli 18.75 (6/32) %, bacilli 9.37 (3/32) % and Corynebacterium spp. 6.25 (2/32) %. The threshold values of modified California mastitis test, total somatic cell count and electrical conductivity in subclinical mastitic milk samples were observed to be +1, 1.0 million cells/ml of milk and 6.0 mS/cm, respectively.